Desa Tangguh Bencana: Peningkatan Kapabilitas Desa Kaloran dalam Menghadapi Bencana Tanah Longsor (Lembaga Pengembangan Kinerja Dosen, 2025)
Kaloran Village is an area characterized by steep slope topography that makes it vulnerable to landslides, especially during the rainy season with high rainfall intensity. Although the landslide risk level in this village is still relatively low and has never caused any casualties, the potential for material losses and psychosocial impacts that may arise still need to be seriously anticipated. Disaster risk reduction efforts in Kaloran Village are carried out through the Disaster Resilient Village Work Program (Destana), which aims to increase the capacity and capability of the community in facing disaster threats. The program implementation method consists of three main stages: preparation through focus group discussions (FGDs) and interviews with stakeholders, preparation of the Destana document containing mitigation strategies and steps, and community empowerment through socialization activities and preparedness training. The results of the study indicate that Kaloran Village is categorized as a Medium Resilient Village with a resilience score of 68.97. This achievement serves as an important basis for strengthening the village preparedness system, which is followed up with the establishment of the Disaster Risk Reduction Forum (FPRB)